Changes in body water content of elite soccer players during the macrocycle according to function on the field - Staskiewicz, W.; Grochowska-Niedworok, E.; Zydek, G.; Kiciak, A.; Bielaszka, A.; Kardas, M.; Bialek-Dratwa, A.; Jaruga-Sekowska, S.; Grajek, M. (Journal of Physical Education and Sport, 2022)
Professional soccer players should meet the physical demands and maintain the best possible performance throughout the season. Body mass composition including body water content has a significant impact on athletes' performance. The aim of this study was to evaluate the changes in body hydration of professional soccer players in all periods of the macro-cycle (preparation, starting, and transition periods) taking into account the position on the field. The study was conducted between January 7, 2021, and July 23, 2021. The participants of the study were players of two soccer sports clubs belonging to PKO BP Ekstraklasa 2020/2021. 38 professional soccer players were included in the study. Body mass composition was assessed using a DSM-BIA electrical bioimpedance analyzer (InBody 770, InBody USA, California, USA). Standards recommended by the manufacturer, InBody USA, and WHO were used to determine TBW [L], ICW [L], ECW [L], and ECW/TBW. The obtained data were processed using Statistica v.13.3 software (Stat Soft Polska). A total of 228 body mass composition measurements were taken in 6 different measurements during the spring round of the 2020/2021 PKO BP Ekstraklasa season. Statistically significantly lower values of total body water, intracellular water, and extracellular water were found in midfielders. TBW content increased between 1 and 6 and 5 and 6 measurements (p<0.01). ICW content was found to increase between 1 and 2 and 1 and 4 measurements (p<0.0001) and ECW content decreased between 2 and 5 measurements (p<0.001). Statistically significant differences were found in the water content measurements of players in different positions. Significantly lower values were found for midfielders. The results of the study showed variation in water content in players playing different positions on the field. The study showed changes in the body hydration of soccer players during the macrocycle (preparatory, competitive, and transitional). No changes in body water content suggesting chronic dehydration of athletes were observed in individual periods of the macrocycle.